Metal Organic Frameworks for Smart Storage and Delivery of Aromatic Volatiles and Essential Oils in Agrifood - Giasemi K. Angeli; Marianna I. Kotzabasaki; Chrysanthos Maraveas (Applied Sciences)
Metal Organic Frameworks (MOFs) are a unique family of tailor-made porous materials that have gained significant attention for their properties and their applications in various fields, including agriculture and agrifood. The aim of this review is to explore the potential of MOFs as smart carriers and delivery mediums of essential oils (EOs) and/or aromatic volatiles. Emphasis is given to their potential to be applied in crop protection and fresh food preservation. MOFs indeed present highly promising physicochemical characteristics in order to be applied in such sectors. To name a few, their high surface area, tunable porosity, and customizable functionalities, make them ideal carriers for EOs, which are established for their antimicrobial properties but their wider practical applications are limited by their volatility and chemical sensitivity. The encapsulation of EOs in MOFs enhances their stability, controlled release, and bioavailability, providing effective solutions for sustainable agriculture and food safety. Furthermore, in this review we discuss various MOF types, emphasizing the most recent literature references, including cyclodextrin-based MOFs, Cu2+ based MOFs, Zn2+ based MOFs as well as Zr4+ MOFs. In this work, we attempt to highlight the interactions and physicochemical characteristics (e.g., pore size and pore functionality), that contribute to the encapsulation of different EOs within MOFs. We focus on a detailed discussion of the external stimuli that can trigger the targeted release of EOs, such as pH changes caused by pathogenic microbial activity. Additionally, we examine the potential benefits of the EOs encapsulation in MOFs, including the reduction of premature evaporation due to their volatile nature and their improved delivery to targeted sites. These aspects are explored within the frameworks’ food safety enhancement, extended shelf life and the promotion of sustainable food preservation alternatives. Furthermore, we address MOFs’ limitations such as biocompatibility, scalability and chemical stability under field conditions to further comprehend their potential as EO carriers in agrifood applications, emphasizing food preservation and protection. Finally, this work aims to contribute to global challenges in nutrition and sustainable agriculture.